If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + 2 + 6x = 3(x + -4) + -1(x + -4) Reorder the terms: 2 + x + 6x = 3(x + -4) + -1(x + -4) Combine like terms: x + 6x = 7x 2 + 7x = 3(x + -4) + -1(x + -4) Reorder the terms: 2 + 7x = 3(-4 + x) + -1(x + -4) 2 + 7x = (-4 * 3 + x * 3) + -1(x + -4) 2 + 7x = (-12 + 3x) + -1(x + -4) Reorder the terms: 2 + 7x = -12 + 3x + -1(-4 + x) 2 + 7x = -12 + 3x + (-4 * -1 + x * -1) 2 + 7x = -12 + 3x + (4 + -1x) Reorder the terms: 2 + 7x = -12 + 4 + 3x + -1x Combine like terms: -12 + 4 = -8 2 + 7x = -8 + 3x + -1x Combine like terms: 3x + -1x = 2x 2 + 7x = -8 + 2x Solving 2 + 7x = -8 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 2 + 7x + -2x = -8 + 2x + -2x Combine like terms: 7x + -2x = 5x 2 + 5x = -8 + 2x + -2x Combine like terms: 2x + -2x = 0 2 + 5x = -8 + 0 2 + 5x = -8 Add '-2' to each side of the equation. 2 + -2 + 5x = -8 + -2 Combine like terms: 2 + -2 = 0 0 + 5x = -8 + -2 5x = -8 + -2 Combine like terms: -8 + -2 = -10 5x = -10 Divide each side by '5'. x = -2 Simplifying x = -2
| 7x-(-2)=47 | | 7(z-7)=6(z+3) | | 9b-36=-3b | | 3+8x-x=10 | | (r-t)(2t+5)= | | 9x+23x-9=8(4x+10) | | 6x(x-10)=0 | | (3*4+8)(5+3n*3)=(6*3+2)(4n+3+5n) | | 7c+2=6c-3(6+c) | | 3x+27x-8=6(5x+9) | | 39n=-2(1-7n) | | 13n+5=96 | | 5h-(h+8)=2h | | -4-6-b=-15 | | 6n-12=21.6 | | -42=-2x-3x-7 | | -4x+3+x=-3 | | 3n-5n=-8(6+5n) | | 2p+m=180 | | 79x+X=720 | | N(p+t)=3298.75 | | 5(3.2)+9(3.2)-2=11(3.2)+7.6 | | X=(15-2)-12 | | 22.24x-33.52=8.91x | | 7(n+3)=24 | | 2(-9-5n)= | | 9y+3000=1500 | | -2-7x=47 | | x=-7x-9 | | 5x+1/2=x+9/4+x-7/4 | | 1/4(x+5)=16 | | 6x+3960=540 |